PENGARUH MODEL GUIDED DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA SMA SANTO FRANSISKUS ASISI PONTIANAK - Berliana, Berliana; Sartika, Rody Putra; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this research was to determine whether there was a difference between learning achievement of students taught using guided discovery learning and conventional learning model, and to determine effect size of guided discovery learning model toward student learning achievement on electrolyte and nonelectrolyte solutions. This research used true experimental with Pretest-Posttest Group Design. The research sample consisted of X IPA 1 class as the experimental group and X IPA 2 class as the control group selected by saturated sampling technique. Learning achievement test, observation sheet and interview guidelines were used to collect data. Based on final questionnaire and posttest data analysis using the Independent Sample t-test (Î± = 5%), Asymp.Sig (2-tailed) were 0.002<0.05. This indicated that there were a difference between learning achievement of students taught using guided discovery learning and conventional learning model. Guided discovery learning model gave 31.33% effect toward student learning achievement. Â Key words: Guided discovery learning, Learning achievement, Electrolyte and nonelecrtrolyte solutions.